A comparison of energetic particle energization observations at MMS and injections at Van Allen Probes - Chepuri, S. N. F.; Jaynes, A. N.; Turner, D. L.; Gabrielse, C.; Baker, D. N.; Mauk, B. H.; Cohen, I. J.; Leonard, T.; Blake, J. B.; Fennell, J. F. (Frontiers in Astronomy and Space Sciences, 2023)
In this study, we examine particle energization and injections that show energetic electron enhancements at both MMS in the magnetotail and Van Allen Probes in the inner magnetosphere. Observing injections along with a corresponding flow burst allows us to better understand injections overall. Searching for suitable events, we found that only a small number of events at MMS had corresponding injections that penetrated far enough into the inner magnetosphere to observe with Van Allen Probes. With the four suitable events we did find, we compared the energy spectra at the two spacecraft and mapped the boundary of where the injection entered the inner magnetosphere. We found that, among these injections in the inner magnetosphere, the electron flux did not increase above ~400 keV, similar to previous results, but the corresponding signatures in the tail observed increased fluxes at 600 keV or higher. There does not appear to be a comparable flux increase at Van Allen Probes and MMS for a given event. None of our injections included ion enhancements at Van Allen Probes, but one included an ion injection at geosynchronous orbit in the GOES spacecraft. All of our injections were dispersed at Van Allen Probes, and we were therefore able to map an estimate of the injection boundary. All of the injections occurred in the premidnight sector. Although we found some events where particle energizations in the tail are accompanied by inner magnetospheric injections, we do not find a statistical link between the two.